(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the role of economic terminology in foreign language teaching in higher education institutions with the integration of digital technologies. The study focuses on the importance of professionally oriented vocabulary in developing students’ communicative competence in academic and professional contexts. It analyzes modern digital tools that facilitate the acquisition of economic terminology, including learning management systems, mobile applications, and artificial intelligence-based platforms. The paper also discusses pedagogical strategies for effectively incorporating specialized vocabulary into language instruction and highlights the advantages and challenges associated with digital learning environments. The findings suggest that the integration of economic terminology through digital technologies enhances students’ motivation, autonomy, and professional readiness.